INDIE-HFpEF (Inorganic Nitrite Delivery to Improve Exercise Capacity in Heart Failure With Preserved Ejection Fraction): Rationale and Design. (May 2017) - Reddy, Yogesh N.V.; Lewis, Gregory D.; Shah, Sanjiv J.; LeWinter, Martin; Semigran, Marc; Davila-Roman, Victor G.; Anstrom, Kevin; Hernandez, Adrian; Braunwald, Eugene; Redfield, Margaret M.; Borlaug, Barry A.
Abstract : Approximately half of patients with heart failure have preserved ejection fraction. There is no proven treatment that improves outcome. The pathophysiology of heart failure with preserved ejection fraction is complex and includes left ventricular systolic and diastolic dysfunction, pulmonary vascular disease, endothelial dysfunction, and peripheral abnormalities. Multiple lines of evidence point to impaired nitric oxide (NO)-cGMP bioavailability as playing a central role in each of these abnormalities. In contrast to traditional organic nitrate therapies, an alternative strategy to restore NO-cGMP signaling is via inorganic nitrite. Inorganic nitrite, previously considered to be an inert byproduct of NO metabolism, functions as an important in vivo reservoir for NO generation, particularly under hypoxic and acidosis conditions. As such, inorganic nitrite becomes most active at times of greater need for NO signaling, as during exercise when left ventricular filling pressures and pulmonary artery pressures increase. Herein, we present the rationale and design for the INDIE-HFpEF trial (Inorganic Nitrite Delivery to Improve Exercise Capacity in Heart Failure with Preserved Ejection Fraction), which is a multicenter, randomized, double-blind, placebo-controlled cross-over study assessing the effect of inhaled inorganic nitrite on peak exercise capacity, conducted in the National Heart, Lung, and Blood Institute–sponsored Heart Failure Clinical Research Network. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02742129.